IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK MENENTUKAN SISWA BERPRESTASI PADA SMK RHOUDHOTU TOLIBIN - Joko Kuswanto; Tri Wardiono; Dapiokta, Jum (Journal of Computer Science and Technology (JCS-TECH), 2026)
Determining outstanding students in school is a crucial process that requires objectivity and accuracy. Outstanding students are not only measured by academic grades, but also involve various aspects such as attitude, discipline, and participation in school activities. Seeing these conditions, it is necessary to have someone who can support decision-making for the selection of outstanding students. This study aims to implement the Simple Additive Weighting (SAW) method to determine outstanding students at SMK Rhoudhotu Tolibin. From the results of the calculations that have been carried out, it can be concluded that the application of the SAW method to determine outstanding students is based on 3 criteria, namely report card scores, attitudes/character and skills